The minimally effective dose of sucrose for procedural pain relief in neonates: a randomized controlled trial - Bonnie Stevens; Janet Yamada; Marsha Campbell-Yeo; Sharyn Gibbins; Denise Harrison; Kimberley Dionne; Anna Taddio; Carol McNair; Andrew Willan; Marilyn Ballantyne; Kimberley Widger; Souraya Sidani; et al. (BMC, 2018)
Abstract Background Orally administered sucrose is effective and safe in reducing pain intensity during single, tissue-damaging procedures in neonates, and is commonly recommended in neonatal pain guidelines. However, there is wide variability in sucrose doses examined in research, and more than a 20-fold variation across neonatal care settings. The aim of this study was to determine the minimally effective dose of 24% sucrose for reducing pain in hospitalized neonates undergoing a single skin-breaking heel lance procedure. Methods A total of 245 neonates from 4 Canadian tertiary neonatal intensive care units (NICUs), born between 24 and 42 weeks gestational age (GA), were prospectively randomized to receive one of three doses of 24% sucrose, plus non-nutritive sucking/pacifier, 2 min before a routine heel lance: 0.1 ml (Group 1; n = 81), 0.5 ml (Group 2; n = 81), or 1.0 ml (Group 3; n = 83). The primary outcome was pain intensity measured at 30 and 60 s following the heel lance, using the Premature Infant Pain Profile-Revised (PIPP-R). The secondary outcome was the incidence of adverse events. Analysis of covariance models, adjusting for GA and study site examined between group differences in pain intensity across intervention groups. Results There was no difference in mean pain intensity PIPP-R scores between treatment groups at 30 s (P = .97) and 60 s (P = .93); however, pain was not fully eliminated during the heel lance procedure. There were 5 reported adverse events among 5/245 (2.0%) neonates, with no significant differences in the proportion of events by sucrose dose (P = .62). All events resolved spontaneously without medical intervention. Conclusions The minimally effective dose of 24% sucrose required to treat pain associated with a single heel lance in neonates was 0.1 ml. Further evaluation regarding the sustained effectiveness of this dose in reducing pain intensity in neonates for repeated painful procedures is warranted. Trial registration ClinicalTrials.gov: NCT02134873. Date: May 5, 2014 (retrospectively registered).